Perancangan Sistem Informasi Manajemen Produksi Padi Berbasis Web untuk Dinas Pertanian Provinsi Aceh - Riza, Muhammad; Ahmad, Lukman; Imilda (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2024)
This research aims to develop an integrated rice production management information system at the Aceh Province Agricultural Service. Old systems that depend on manual form filling have hampered efficiency and accuracy in data collection and processing. In this research, system analysis and design methods are used to design a new system that includes features such as land area management, rice production, and rice productivity. System testing is carried out using the black-box testing method to ensure the expected functionality is met. Test results show that most system features have passed the test, although some features require further improvement. Based on the test results, the percentage of test success was 66.67%. Overall, the rice production management information system that has been developed can assist the Aceh Provincial Agriculture Service in managing rice production data more efficiently. Some of the suggestions proposed include improvements to features that do not pass testing, training and outreach to system users, increasing data security, developing additional features, as well as regular evaluation and monitoring. It is hoped that implementation of these suggestions will improve the quality and benefits of the system for users.